The Language of Responsibility in the United Nations Security Council, 1946–2020. - Bethke, Felix S; Haass, Felix; Niemann, Holger (International Studies Quarterly, 2024)
The United Nations Security Council (UNSC) is the United Nations' most powerful institutional body, charged with the "primary responsibility for the maintenance of international peace and security." The main instrument through which the Council asserts this power is its resolutions, specifically by using resolution text to attribute responsibility. The UNSC uses responsibility language to assign tasks, identify accountability under international law, or reflect the Council's normative interpretation of political principles. Yet we lack a comprehensive empirical description of responsibility attributions in UNSC resolutions. We address this gap by providing an original dataset of the full text of all UNSC resolutions between 1946 and 2020. We use this data to show that the Council has significantly increased responsibility attributions since the end of the Cold War, but only for a very specific subset of terms, targeting predominantly states and individuals. We further demonstrate how the data can inform debates about the timing and status of the "responsibility to protect" as an international norm. The data and findings provide a helpful starting point for many future research endeavors, including the role of member states in the UNSC, quantitative and qualitative research on UNSC decision-making processes, or topic development of the UNSC agenda in general.